2020
DOI: 10.1136/bmjopen-2020-039501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytokines as a biomarker to distinguish active tuberculosis from latent tuberculosis infection: a diagnostic meta-analysis

Abstract: ObjectivesWith a marginally effective vaccine and no significant breakthroughs in new treatments, a sensitive and specific method to distinguish active tuberculosis from latent tuberculosis infection (LTBI) would allow for early diagnosis and limit the spread of the pathogen. The analysis of multiple cytokine profiles provides the possibility to differentiate the two diseases.DesignSystematic review and meta-analysis.Data sourcesPubMed, Cochrane Library, Clinical Key and EMBASE databases were searched on 31 De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…A systematic meta-analysis by Sudbury et al (2020) measured 100 cytokines among 56 included studies and found that the most frequently studied cytokines were IFN-γ, IL-2, TNF-α, IP-10, IL-10, and IL-13. A meta-analysis by Qiu et al (2020) evaluated seven cytokines, including IFN-γ, TNF-α, IP-10, IL-2, IL-10, IL-12, and VEGF, suggesting that cytokines IL-2, IFN-γ, and VEGF can be utilized as promising biomarkers to distinguish LTBI from aTB. Furthermore, compared to IFN-γ, the level of IP-10 was higher and was released independently of age, suggesting that IP-10 may be a candidate biomarker in the pediatric population (Alsleben et al, 2012).…”
Section: Cytokinesmentioning
confidence: 99%
“…A systematic meta-analysis by Sudbury et al (2020) measured 100 cytokines among 56 included studies and found that the most frequently studied cytokines were IFN-γ, IL-2, TNF-α, IP-10, IL-10, and IL-13. A meta-analysis by Qiu et al (2020) evaluated seven cytokines, including IFN-γ, TNF-α, IP-10, IL-2, IL-10, IL-12, and VEGF, suggesting that cytokines IL-2, IFN-γ, and VEGF can be utilized as promising biomarkers to distinguish LTBI from aTB. Furthermore, compared to IFN-γ, the level of IP-10 was higher and was released independently of age, suggesting that IP-10 may be a candidate biomarker in the pediatric population (Alsleben et al, 2012).…”
Section: Cytokinesmentioning
confidence: 99%
“…We chose in our study to measure cytokines/chemokines released in response to mycobacterial antigens to increase the specificity for TB. A few studies already addressed this question by measuring chemokines/cytokines induced by the peptides from the QuantiFERON, with different marker selections among the studies ( 13 ). Our results are difficult to compare to these studies, as we selected combinations of chemokines/cytokines induced by two different stage-specific mycobacterial antigens, ESAT-6 and HBHA, in order to cover a wide range of the M. tuberculosis metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous proteins evaluated, the mycobacterial heparin-binding haemagglutinin (HBHA, Rv0475) appears as one of the most promising antigens to differentiate LTBI from aTB, but only few studies assessed HBHA-induced cytokines other than IFN-γ ( 10 12 ). In contrast, the potential added value of various cytokines induced by the peptides of the commercial IGRAs has been investigated, but with conflicting outcomes, as highlighted by a recent meta-analysis ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis on the diagnostic accuracy of IFN-γ for differentiating ATB from TBI showed an overall pooled sensitivity, specificity, negative likelihood rate (NLR), positive likelihood rate (PLR), diagnostic odds ratio (DOR), and area under curve (AUC) of 0.72, 0.82, 0.34, 4.0, 12.00, and 0.84, respectively [ 136 ].…”
Section: Evaluation Of Host-derived Biomarkersmentioning
confidence: 99%